2015
DOI: 10.1007/s13410-015-0417-x
|View full text |Cite
|
Sign up to set email alerts
|

Infections and diabetes

Abstract: Infections and diabetes illustrate the health problems facing India, and more. The two often coexist, making each other the worse for it. Subjects with diabetes have a greater frequency and severity of many common infections (urinary, pulmonary, soft tissue) whereas some rare infections are seen almost exclusively in the diabetic population viz. rhino-cerebral mucormycosis, malignant otitis-externa and emphysematous cholecystitis, cystitis, and pyelonephritis.These infections should be sought in patients prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 35 publications
0
4
0
1
Order By: Relevance
“…In contrast to the current study, a previous study reported that malignancy was protective against CRKP infection, especially in patients hospitalized under isolation conditions. 31 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to the current study, a previous study reported that malignancy was protective against CRKP infection, especially in patients hospitalized under isolation conditions. 31 …”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the current study, a previous study reported that malignancy was protective against CRKP infection, especially in patients hospitalized under isolation conditions. 31 Diabetic patients are more prone to developing infections due to abnormal vascularity, autonomic function, cell-mediated immunity, and phagocytic function. 32 Patients with CVDs may be at an increased risk of CRKP infection due to frequent hospitalizations and invasive interventions.…”
mentioning
confidence: 99%
“…Poor glycemic control contributed to nearly two quarters (23/31; 74.19%) of the total amputees. In the diabetic population chronic hyperglycemia leads to impaired wound healing due to increased susceptibility to infections, chronic inflammation state, diabetic micro and macro-angiopathy leading to diminished vascularity, impaired collagen synthesis, impaired hyaluronan, autonomic dysfunction and abnormality in cell-mediated immunity and phagocytic function [ 13 , 14 ]. A high glycated hemoglobin also impairs endothelium mediated vasoactive responses.…”
Section: Discussionmentioning
confidence: 99%
“…Most cases of diabetic foot infection have been shown to be polymicrobial in nature, with predominance of Gram-negative organisms [ [15] , [16] , [17] ]. Prevalence of antimicrobial drug resistance was also found to be higher among patients with diabetes, which could be attributed, at least partially, to the production of biofilms by the causative organisms [ 18 ].…”
Section: Common Infections In Individuals With Diabetesmentioning
confidence: 99%